The "Champagne Tower" of Science Publishing - Siebert, Sabina (International Higher Education, 2018)
This article discusses the hierarchical nature of science publishing, whereby journals are organized in tiers with the most prestigious elite journals at the top (Cell, Nature, Science), and lowest-ranked journals at the bottom. When rejected from the top-tier journals, authors usually aim for a lower tier of journals, with some choosing smaller, specialist journals for the outlet of their work. Recently, however, a different mechanism of cascading the papers down the hierarchy of journals has become popular, i.e., editors arrange to pass the rejected papers, with the authors’ permission, to their “sister journals” bearing the same brand. These transfer arrangements may be seen beneficial for the authors, as they reduce the publication time, but they also pose difficulties for smaller specialist journals that lose their share of the market and experience a fall in manuscript submissions.